Computer remote monitoring via mobile phones using socket programming / Samih Omer Fadlelmola Elkhider - Omer Fadlelmola Elkhider, Samih (2011)
Presently, many researches have been made on remote monitoring and its techniques. The studies show beyond technical algorithms, physical aspects plays a big rule in client server model. Sockets programming is one f the most basic and useful method of achieving any client server connectivity. The approach of the mobile cloud is clearly occurring with web host servers expands thus large number of data around the world stored in huge servers, consumers of mobile devices and small computing devices have high performance expectations usually, therefore mobile cloud computing theorizes that the cloud will soon become a disruptive force in the mobile world, eventually becoming the dominant way in which mobile applications operates. In this dissertation a mobile cloud will be under consideration when designing the prototype, it is proven that mobile processors are tiny processors and could only handle a limited resources, thus the ability of making the applications processes in server, leaving the mobile clients a small part of only accessing data and interact with it. Such methodology can be achieved by java programming language for mobile clients J2ME, and by using a second generation mobile phones. Moreover, this prototype could be used as the basis for developing more advanced remote monitoring in term of performance to access and interact with mobile cloud, which is the future of mobile technology.